Upaya Mewujudkan Wisata Kolam Renang Kucur Aren Menjadi Destinasi Wisata Favorit di Desa Wonokerto - Najmuddin, M. Naufal; Mufarid, Kafani Safrul; Adilin, Mochammad Luthfan; Chalil, M.; Husain, Muhammad Ajid (CV. ITTC INDONESIA, 2023)
Abstract The actual phenomenon in the field proves that the existence of the Kucur Aren Swimming Pool has not been well known by the wider community. Even though the Kucur Aren Swimming Pool is located in a strategic area, namely the Wonosalam District, Jombang Regency, which is famous for its beautiful tourism potential, it is not enough to attract tourists to come to the Kucur Aren Swimming Pool. This is caused by several factors, one of which is the lack of maintenance of governance and the lack of publication of the Kucur Aren Swimming Pool. Therefore, community service activities are focused on revitalization as well as empowerment to improve maintenance of the management of the Kucur Aren Swimming Pool and re-publication or rebranding of the Kucur Aren Swimming Pool. The implementative steps that have been taken include: (1) Exploring the root causes of the management of the Kucur Aren Swimming Pool tourism management through observation and interviews with managers; (2) Provide recommendations for maintenance and management of Kucur Aren Swimming Pool tourism to Kucur Aren Swimming Pool tourism managers; (3) Organizing an introduction to the Kucur Aren Swimming Pool tour to the community; (4) Carry out revitalization and cleaning of inappropriate tourist objects; (5) Submitting a Proposal containing a Master Plan to the Jombang District Youth, Sports and Tourism Office for the long-term sustainability of the Kucur Aren Swimming Pool tour.